Identifying objects impairs knowledge of other objects: A relearning explanation for the neural repetition effect - Marsolek, Chad J.; Deason, Rebecca G.; Ketz, Nicholas A.; Ramanathan, Pradeep; Bernat, Edward M.; Steele, Vaughn R.; Patrick, Christopher J.; Verfaellie, Mieke; Schnyer, David M. (NeuroImage (Orlando, Fla.), 2010)
Different items in long-term knowledge are stored in the neocortex as partially overlapping representations that can be altered slightly with usage. This encoding scheme affords well-documented benefits, but potential costs have not been well explored. Here we use functional magnetic resonance imaging (fMRI), neurocomputational modeling, and electrophysiological measures to show that strengthening some visual object representations not only enhances the subsequent ability to identify those (repeated) objects—an effect long known as repetition priming—but also impairs the ability to identify other (non-repeated) objects—a new effect labeled antipriming. As a result, the non-repeated objects elicit increased neural activity likely for the purpose of reestablishing their previously weakened representations. These results suggest a novel reevaluation of the ubiquitously observed repetition effect on neural activity, and they indicate that maintenance relearning may be a crucial aspect of preserving overlapping neural representations of visual objects in long-term memory.